An advance understanding of the alkali activation of cover layers waste rocks from phosphate mines: Mechanical, structure and microstructure studies. (5th September 2022) - Sbi, Sanae; Aboulayt, Abdelilah; Borja, Wafaa; Mansouri, Said; El Boudour El Idrissi, Hicham; Samih, Youssef; Semlal, Nawal; Hannache, Hassan; Tamraoui, Youssef; Alami, Jones
Highlights: Phosphate mining wastes rocks as a promising secondary resource material in civil engineering. Depper understanding of alkali activation of Phosphate mining waste rocks from the cover layer. Phase composition investigated through MAS NMR-based analyses. Formation of various hydration products, including CSH, C-(A)-SH, N-(A)-SH and C-(N)-ASH gels. Abstract: This study details the effect of silica modulus variation (SiO2 /Na2 O 1.25, 1.50 and 1.75) on the mechanical properties and the microstructure evolution of Alkali Activated Materials (AAM) based on phosphate mining waste rocks and issued from the cover layer. The mechanical behavior of samples was assessed by compression and flexural strength tests at 7 and 28 days of curing. A resulting highly compact microstructure was formed by decreasing the silica modulus (Ms), leading to an enhancement of the mechanical strength. The microstructure of hardened specimens was studied using X-ray Diffraction (XRD), Fourier Transform InfraRed (FTIR), Scanning Electron Microscopy (SEM), Energy-Dispersive X-ray spectroscopy (EDX) and 29 Si, 27 Al, 23 Na Magic Angle Spinning Nuclear Magnetic Resonance (MAS NMR). The results show the formation of CSH gels as main reaction products, C–(A)–SH and N–(A)–SH gels, with the possible formation of a hybrid C–(N–A)–SH gels. The structure of these formed gels appears to depend on the raw material's chemical composition, as confirmed by MAS NMR and SEM/EDX analysis. These results provide insight in alkali activation of phosphate mining waste from the cover layer, which can promote their valorization in several construction applications, and consequently, contribute to sustainable phosphate mining..